Low-Cost Dye-Sensitized Solar Cells Based on TiO2 Nanoparticles Downscaled by Optimized Wet Milling Process - Arnold Anthony Huamán Aguirre; María Esther Quintana Cáceda; Juan Martin Rodriguez Rodriguez; Walter Francisco Estrada Lopez (Fundamental Research and Application of Physical Science Vol. 1, 2023)
In order to show the contributions that this top-down technique can provide for the production of photoelectrodes, the efficiency results of the solar cells developed from the post-milling powders are presented. Wet milling, which is regarded as a top-down method of nanotechnology, was used to create TiO2 nanoparticles from highly pure anatase. The performance of polyethylene glycol (PEG400) as a dispersing agent in the milling system was also assessed, along with the impact of the main operating parameters of wet milling on the particle size distribution of the finished product. The results showed that the processes that use polyethylene glycol achieved a higher particle fragmentation. This could be observed in the histograms made from SEM images taken from the final samples whose populations reached an average size of approximately 90nm. The TiO2 nanoparticles obtained by grinding were used in the fabrication of dye-sensitized solar cells. It was verified that the nanoparticles produced with the dispersing agent achieved the highest efficiencies, the highest being 0.94% with an appreciable open circuit voltage of 0.81V. The best efficiencies were achieved by the cells manufactured with the powders and in whose manufacture the dispersing agent was used. Furthermore, the smaller particle sizes were achieved for these processes.